A Stromal Lysolipid-Autotaxin Signaling Axis Promotes Pancreatic Tumor Progression - Auciello, Francesca R; Bulusu, Vinay; Oon, Chet; Tait-Mulder, Jacqueline; Berry, Mark; Bhattacharyya, Sohinee; Tumanov, Sergey; Allen-Petersen, Brittany L; Link, Jason; Kendsersky, Nicholas D; Vringer, Esmee; Schug, Michelle; et al. (Cancer discovery, 2019)
Pancreatic ductal adenocarcinoma (PDAC) develops a pronounced stromal response reflecting an aberrant wound-healing process. This stromal reaction features transdifferentiation of tissue-resident pancreatic stellate cells (PSC) into activated cancer-associated fibroblasts, a process induced by PDAC cells but of unclear significance for PDAC progression. Here, we show that PSCs undergo a dramatic lipid metabolic shift during differentiation in the context of pancreatic tumorigenesis, including remodeling of the intracellular lipidome and secretion of abundant lipids in the activated, fibroblastic state. Specifically, stroma-derived lysophosphatidylcholines support PDAC cell synthesis of phosphatidylcholines, key components of cell membranes, and also facilitate production of the potent wound-healing mediator lysophosphatidic acid (LPA) by the extracellular enzyme autotaxin, which is overexpressed in PDAC. The autotaxin-LPA axis promotes PDAC cell proliferation, migration, and AKT activation, and genetic or pharmacologic autotaxin inhibition suppresses PDAC growth . Our work demonstrates how PDAC cells exploit the local production of wound-healing mediators to stimulate their own growth and migration. SIGNIFICANCE: Our work highlights an unanticipated role for PSCs in producing the oncogenic LPA signaling lipid and demonstrates how PDAC tumor cells co-opt the release of wound-healing mediators by neighboring PSCs to promote their own proliferation and migration. . .